El aprendizaje autodirigido y la Flipped Classroom - Briones Galarza, Carlos (2014)
The purpose of this study was to use the flipped classroom to improve student achievement in the unit of linear momentum, and to determine the level of self-directed learning. Opting to focus on engineering careers at an Ecuadorian university, 74 students, between the of ages 17 and 19 years old, and enrolled in a Physics Leveling Course, participated in this study. The researchers worked with two intact groups; in one group the independent variable was applied and in the other group the independent variable was not applied. Both groups received the same content. The experimental group was instructed according to the pedagogical model of the flipped classroom, and the control group was instructed according to the traditional teaching model. The two groups were given a pre and post test based on the contents and a self-directed learning questionnaire. The investigation found that the flipped classroom improves student learning and encourages self-directed learning.